Clinical Study of Brihatsindooradya Taila and its Malahar on Kustha w.s.r. to Chronic Plaque Psoriasis - Sumitra; Kumar, Sanjay; Rajoria, Kshipra; Verma, Vijay Shankar (International Research Journal of Ayurveda & Yoga, 2022)
Background: In Ayurveda, skin ailments are categorized as "kustha." In skin diseases, external use of drugs is just as important as internal therapy because it may provide greater and faster symptom relief. Acharya Sushrut while prescribing the treatment for kustha according to dhatugatawa, mentioned shodhan and alepana as first choice of management for twakgata kustha hence lepana karma has been considered as an ideal therapeutic measure for these diseases. Aim: The aim was to evaluate the role of Ayurveda treatment modalities in Kushtha. To conduct the pharmaceutical – analytical study on BST and its malahar .To study the comparative efficacy of Brihatsindoordya Taila (BST) and its malahar in the management of kustha w.s.r.to chronic plaque psoriasis. Materials and Methods: The study was prospective, interventional with Randomized, Open labelled, Controlled trial and conducted in 30 clinically diagnosed patients with classical sign and symptoms of kushtha .The study was conducted on 30 clinically diagnosed patients of Kushtha divided into 2 groups having 15 patients in each group. Total 30 patients of kustha w.s.r. to chronic plaque psoriasis had been randomly divided into two groups was given Brihatsindoordya Taila (BST) & Brihatsindoordya Taila Malahar ( BSM ) for topical administration, twice a day, for a duration of 30 days respectively. Results: The observations and results concluded that drug i.e BST & BSM showed effective and highly significant results in signs and symptoms of Kushtha i.e (p<0.0001). Conclusion: This case study revealed the efficacy of Ayurveda therapy, including external, for 1 month in the management of Kushtha. Keywords: Chronic plaque psoriasis, Eka-Kushtha, Shamana, Shodhana. The study reveals that combination of Ayurvedic modalities gives significant result in lakshnas (Symptoms) like Aswedana, Mahavastu, MastyaShakalopama.